2016
DOI: 10.1653/024.099.0128
|View full text |Cite
|
Sign up to set email alerts
|

Trichogramma(Hymenoptera: Trichogrammatidae) Species, Egg Parasitoids ofDiatraea saccharalis(Lepidoptera: Crambidae) on Sugarcane (Poales: Poaceae) in Argentina

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In Tucumán province the parasitism of D. saccharalis eggs is due to Trichogramma spp. (Hymenoptera: Trichogrammatidae) (Isas et al ., 2016) and its presence period in sugarcane crop does not overlap with burnings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tucumán province the parasitism of D. saccharalis eggs is due to Trichogramma spp. (Hymenoptera: Trichogrammatidae) (Isas et al ., 2016) and its presence period in sugarcane crop does not overlap with burnings.…”
Section: Discussionmentioning
confidence: 99%
“…The natural enemies of D. saccharalis in Tucumán are several species of Trichogramma genera (eggs parasitoids) (Hymenoptera: Trichogrammatidae), Paratheresia claripalpis (Diptera: Tachinidae), Jayneleskia jaynesi (Diptera: Tachinidae), Agathis sp. (Hymenoptera: Braconidae) and Iphiaulax tucumanus (Hymenoptera: Braconidae) (larval parasitoids) (Box, 1927; Hayward, 1943; Willink et al ., 1991; Pérez et al ., 2010; Isas et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, after the first three days of parasitism, differences were apparent between the isolines selected in D. saccharalis eggs (ATP-I) and the non-selected strain. This finding suggested that the results could be different if the T. atopovirilia strain assessed was the same collected in Brazil (states of Tocantins and Piauí) or Argentina, where it naturally parasitized D. saccharalis (Silva et al, 2018 unpublished data;Isas et al, 2016) rather than the strain kept at labotratory condition, which was originally collected in the state of Paraná (Brazil) parasitizing H. zea eggs. Alternatively, if the initial population of T. atopovirilia had higher genetic variability, although kept in laboratory for a few generations, the possibility of finding a more aggressive haplotype toward D. saccharalis is greater.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…Trichogramma atopovirilia has been reported parasitizing eggs of D. saccharalis in rice fields in the states of Tocantins and Piauí, northern and northeastern Brazil (Silva, 2018, unpublished data), and in the Tucumán province in Argentina (Isas et al, 2016). According to Browning and Melton (1987), parasitism of T. atopovirilia in D. saccharalis eggs is low compared to T. fuentesi Torre.…”
Section: Introductionmentioning
confidence: 99%
“…Trichogramma galloi Zucchi (Hymenoptera: Trichogrammatidae) is the main biological control agent of Diatraea saccharalis Fabricius (Lepidoptera: Crambidae) in sugarcane cultures (Isas et al 2016). However, Trichogramma spp.…”
Section: Introductionmentioning
confidence: 99%